Teplice program--the impact of air pollution on human health - Srám, R J; Benes, I; Binková, B; Dejmek, J; Horstman, D; Kotĕsovec, F; Otto, D; Perreault, S D; Rubes, J; Selevan, S G; Skalík, I; Stevens, R K; et al. (Environmental health perspectives, 1996)
The aim of the Teplice Program is to investigate and assess the impact of air pollution on the health of the population in the district of Teplice, Czech Republic. Characterization of the air pollutants demonstrated unusually high concentrations during winter inversions of fine particles dominated by acidic sulfates, genotoxic organic compounds, and toxic trace elements. The major source of airborne fine particles is the burning of coal for heating and power. Human exposure and biomarker studies demonstrated large seasonal variations in air pollution within the Teplice District and higher seasonal average pollution levels than the comparative district, Prachatice. Personal exposures to fine particles and organic carcinogens [e.g., polycyclic aromatic hydrocarbons (PAH)] were correlated with excretion of PAH metabolites in urine, several trace metals in blood, and DNA adducts in white blood cells. Respiratory and neurobehavioral studies of school children were conducted using questionnaires and clinical measures. A significantly higher prevalence of adverse respiratory symptoms and decreased lung function were found in the Teplice district than in Prachatice. The neurobehavioral studies indicated significantly higher teacher referrals for clinical assessment in Teplice, but the majority of objective performance measures did not differ. Reproductive studies were conducted in both males and females. A study of the effects of exposure on pregnancy and birth found an excess prevalence of low birth weight and premature births in Teplice; these adverse effects were more common in infants conceived in the winter and whose mothers were smokers. Based on questionnaires and medical examination, the reproductive development of young men was not different between districts and seasons, however, measures of semen quality suggest that exposure to high levels of air pollution are associated with transient decrements in semen quality.
Keywords: zdraví; Male; biologické markery; Child, Preschool; Biomarkers; Česká republika; Pregnancy; těhotenství; Child Welfare; výsledek těhotenství; mužské pohlaví; Air Pollution; Respiration; Czech Republic; sperma; sociální péče o dítě; předškolní dítě; Semen; znečištění ovzduší; Pregnancy Outcome; lidé; ženské pohlaví; Humans; Environmental Exposure; Female; dýchání; vystavení vlivu životního prostředí; Health